The manager's pocket guide to knowledge management - Curley, Kathleen Foley (HRD Press, 2001)
Knowledge about customers, markets, core processes, how things get done, who knows what is a core business asset. You may have heard of knowledge management. No longer a buzz word, it's becoming mainstream in companies large and small who want to strengthen core competencies in: Responsiveness to the market; Innovation of new products and services; Competency of skill base; Efficiency of work processes. If you're ready to start the knowledge management process in your organization, this book provides a practical plan and roadmap. You'll walk through all the stages - assessment, planning, deployment, and evaluation - and gain specific action steps for putting it all together to expand your core competency and win competitive advantage.